The relationship between patients' personality traits, the alliance, and change in interpersonal distress in intensive group treatment for personality dysfunction - Aafjes-van Doorn, Katie; Kealy, David; Ehrenthal, Johannes C.; Ogrodniczuk, John S.; Joyce, Anthony S.; Weber, Rainer (Journal of personality disorders, 2022)
This study examined patients' personality traits as operationalized by the five-factor model in relation to early alliance and reduction of interpersonal distress through an intensive group treatment program for personality dysfunction. A sample of 79 consecutively admitted psychiatric outpatients with personality dysfunction who attended an 18-week intensive group treatment program completed the NEO Five-Factor Inventory at pretreatment, the Inventory of Interpersonal Problems at pre- and posttreatment, and the Edmonton Therapeutic Alliance Scale, a measure of the therapeutic alliance with the program therapist, at Session 5. Results indicated that patients who were relatively extraverted tended to rate the alliance with their program therapist higher and subsequently reported more improvement of interpersonal distress. The presence of a personality disorder did not moderate this mediation. Patients' extraversion likely promotes a bonding with the therapist and facilitates the interpersonal group work necessary for improvement. Assessing patients' level of extraversion before starting intensive group treatment might indicate which intervention strategies could be useful with that patient within the program frame.